THE PROMINENT WINNERS AND PRIZE-WINNERS OF ART COMPETITIONS AT THE OLYMPIC GAMES OF THE MODERN AGE - Ivanna Lytvynets; Bogdan Vynogradskiy; Anton Lytvynets; Iuliia Pavlova (Lesya Ukrainka Volyn National University, 2017)
The current relevance of the research. The history of the sport movement of the early twentieth century is characterized by a special phenomenon - a combination of Sport and Art. The Olympic Art Competitions are one of the most important cultural events of the age that was realized in the program of the Olympic Games. The article highlights the achievements of the prominent figures of the Olympic Art Competitions, which were held during the Olympic Games from 1912 to 1948. The aim of this study was to characterize the achievements of the outstanding figures at the Olympic Art Competitions. Methods: analysis and generalization of scientific literary sources, historical, theoretical interpretation. Results. The achievements of the prominent figures at the Olympic Art Competitions have been investigated. There are the presidents of the International Olympic Committee (Pierre de Coubertin, Avery Brundage), the multiple winners and prize-winners of Art Competitions (Jean Jacoby, Alex Walter Diggelmann, Werner March, Josef Petersen), the champions of the Olympic Games in sport competitions (Walter Winans, Alfred Hajos), the authors of the constructed sport facilities (Jan Wils, Walter March, Werner March) among them. Conclusions. It has been found out that during the period 1912-1948 the winners of the Olympic Art Competitions were leaders from 23 countries of the world. The total number of the awards won was 49 gold, 53 silver and 49 bronze ones. Two Presidents of the International Olympic Committee (Pierre de Coubertin, Avery Brundage) were discovered to participate in the Olympic Art Competitions. Luxembourg artist Jean Jacoby (2 gold awards), Swiss artist Alex Walter Diggelmann (1 gold, 1 silver, 1 bronze medal), Danish writer Josef Petersen (3 silver awards), German architect Werner March (1 gold and 1 silver medal) were stated to be the most successful participants in the Olympic Art Competitions. People of art were proved not to be the only ones to compete at the Olympic Art Competitions.  In the history of the Olympic Games two participants were both sport winners and Art Competitions winners (Walter Winans, Alfred Hajos).